2018
DOI: 10.1002/mrm.27623
|View full text |Cite
|
Sign up to set email alerts
|

Fast high‐resolution brain metabolite mapping on a clinical 3T MRI by accelerated H‐FID‐MRSI and low‐rank constrained reconstruction

Abstract: Purpose Epitomizing the advantages of ultra short echo time and no chemical shift displacement error, high‐resolution‐free induction decay magnetic resonance spectroscopic imaging (FID‐MRSI) sequences have proven to be highly effective in providing unbiased characterizations of metabolite distributions. However, its merits are often overshadowed in high‐resolution settings by reduced signal‐to‐noise ratios resulting from the smaller voxel volumes procured by extensive phase encoding and the related acquisition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 54 publications
(161 reference statements)
5
46
0
Order By: Relevance
“…The present study did not directly compare this acquisition to others at 3Tesla in which the nominal resolution ranged from 300 μL (31) to 1000 μL (32). However, the resulted nominal resolution and metabolite maps achieved in this study are comparable (62.5 μL vs 40 μL) to the ones in which constrained reconstruction methods with FID acquisition were used (33,34). The achieved nominal resolution and provided metabolite maps within 9 minutes 36 seconds are also comparable with the ultra-high-field (UHF ≥ 7T) ones with nominal voxel sizes of 23 μL (35).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The present study did not directly compare this acquisition to others at 3Tesla in which the nominal resolution ranged from 300 μL (31) to 1000 μL (32). However, the resulted nominal resolution and metabolite maps achieved in this study are comparable (62.5 μL vs 40 μL) to the ones in which constrained reconstruction methods with FID acquisition were used (33,34). The achieved nominal resolution and provided metabolite maps within 9 minutes 36 seconds are also comparable with the ultra-high-field (UHF ≥ 7T) ones with nominal voxel sizes of 23 μL (35).…”
Section: Discussionsupporting
confidence: 61%
“…Thus, we believe that our strategy offers substantial resolution improvement compared to the other implementations at 3T and UHF. With the use of constrained reconstruction methods, the proposed strategy is expected to provide higher resolution (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…6 For high spectral bandwidths, the self-rewinding and constant-angular velocity properties of CRTs render them more SNR-efficient, faster, and less susceptible to gradient imperfections than other spatial-spectral encoding approaches. Although 3T MRI scanners are more widely available, so far only a few studies have used CRTs, 7,8 only 2 studies used FID-MRSI, 9,10 and no application has yet been reported for a combination of both at 3T. Besides being highly beneficial for clinical application, preliminary results 11 also raise the hope that the efficient combination of FID-MRSI and rapid CRT encoding could provide 3D mapping of glutamate with temporal and spatial resolutions high enough to observe stimuli-induced changes via functional MRSI.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, exploiting the Hankel low‐rank structures induced by the linear predictability properties in spectroscopy data may offer additional benefits . More advanced strategies to impose spatial prior information can also lead to potential improvements in SNR, and/or further reduction of artifacts (e.g., residual nuisance signals and spectral distortion) . The current subspace learning strategy assumes consistent subspace structures across different subjects (even when individual voxel spectra vary).…”
Section: Discussionmentioning
confidence: 99%